Confirmatory Factor Analysis and Temporal Invariance of the Positive and Negative Affect Schedule (PANAS) - Galinha, Iolanda Costa (2014)
This paper analyzes the structure and the temporal invariance of the Portuguese version of the Positive and Negative Affect Schedule. Previous studies are not consensual whether PANAS measures two or three affect factors and whether such factors are independent or correlated. In order to fi ll in this gap, we compared the original PANAS, as an independent bi-dimensional structure, with several other alternative structures. Two hundred forty fi ve university students and professional trainees answered the questionnaire in two distinct moments with a two month interval. The model of PANAS with a structure of two independent factors, Positive Affect (PA) and Negative Affect (NA), as proposed by the authors of the scale, was tested. However, the best model consisted of two independent factors, PA and NA, with the cross-loading of the item “excited” between PA and NA, and specifi ed error correlations between the same categories of emotions. Another gap in the literature is the temporal invariance analysis of the PANAS. This paper assesses the temporal invariance of the scale, using the structural equation modeling analysis. Although it was used in its state form version, the PANAS scale showed temporal stability in a two month interval.